Screening and fractionation of plant extracts with antiproliferative activity on human peripheral blood mononuclear cells - Elaine M Souza-Fagundes; Ana BR Queiroz; Olindo Assis Martins Filho; Giovanni Gazzinelli; Rodrigo Corrêa-Oliveira; Tânia MA Alves; Carlos L Zani (Memorias do Instituto Oswaldo Cruz, 2002)
Three hundred and thirteen extracts from 136 Brazilian plant species belonging to 36 families were tested for their suppressive activity on phytohemaglutinin (PHA) stimulated proliferation of human peripheral blood mononuclear cells (PBMC). The proliferation was evaluated by the amount of [³H]-thymidine incorporated by the cells. Twenty extracts inhibited or strongly reduced the proliferation in a dose-dependent manner at doses between 10 and 100 µg/ml. Three of these extracts appeared to be non-toxic to lymphocytes, according to the trypan blue permeability assay and visual inspection using optical microscopy. Bioassay-guided fractionation of Alomia myriadenia extract showed that myriadenolide, a labdane diterpene known to occur in this species, could account for the observed activity of the crude extract. Using a similar protocol, an active fraction of the extract from Gaylussacia brasiliensis was obtained. Analysis of the ¹H and13C NMR spectra of this fraction indicates the presence of an acetylated triterpene whose characterization is underway. The extract of Himatanthus obovatus is currently under investigation.